Exploring distribution and genomic diversity of begomoviruses associated with yellow mosaic disease of legume crops from India, highlighting the dominance of mungbean yellow mosaic India virus - Akram, Mohammad; Kamaal, Naimuddin; Pratap, Aditya; Kumar, Deepender; Muin, Abdul; Sabale, P. R.; Aidbhavi, Revanasidda; Sunani, Sunil Kumar; Rathore, Meenal; Gupta, Sanjeev; Singh, N. P.; Dey, N.; et al. (Frontiers in Microbiology, 2024)
Yellow mosaic disease (YMD) caused by several begomoviruses is one of the major constraints of over a dozen leguminous crops worldwide, particularly in Asian and Southeast Asian countries. The present study aimed to investigate the distribution, diversity and prevalence of begomoviruses associated with YMD in leguminous hosts in five agro-climatic zones of India, to assess the extent of their geographical presence and develop location and crop-specific distribution maps. One hundred and seventy-four leguminous plant samples were tested from 32 locations in India to detect YMD-causing viruses. Additionally, publicly available data were incorporated into this study to provide a comprehensive overview of their distribution in India. This resulted in 581 reports on the DNA-A component representing 119 locations, which were also utilized to depict the distribution of YMD-causing viruses on a map of India. In this study, 117 full-length DNA-A and 103 DNA-B components were successfully characterized, representing the detected mungbean yellow mosaic India virus (MYMIV), mungbean yellow mosaic virus (MYMV), and horsegram yellow mosaic virus in the collected samples. Phylogenetic analysis of isolates of these species showed no differentiation based on location in India. Diversity indices revealed the abundance (55.9%) and dominance (0.56) of MYMIV across 119 locations. These findings hold significant implications for legume researchers, offering insights into disease prevalence and geographic distribution. Furthermore, the distribution of YMD-causing viruses in different agro-climatic zones will help researchers in developing zone-specific YMD-resistant cultivars of the legume crops and would facilitate effective disease management options.